Baseline polysaccharide-specific antibodies may not consistently inhibit booster antibody responses in infants to a serogroup C meningococcal protein-polysaccharide conjugate vaccine. - Blanchard-Rohner, G; Watt, H; Kelly, D; Yu, L; Snape, MD; Pollard, A (2012)
Negative correlations between baseline antibody concentrations and increases in antibody concentrations (after booster doses of vaccines) have been reported previously. Such correlation coefficients are widely reported by statisticians to be subject to mathematical coupling. Negative correlations may be attributable partly or wholly to the combination of mathematical coupling and measurement error (or other short term fluctuations in measurements) and therefore not clinically interpretable. In this study we re-analysed the serum antibody responses from five clinical trials of serogroup C meningococcal conjugate vaccine (MenCV) given to infants for priming followed by boosting with MenCV or a meningococcal A/C polysaccharide vaccine (MenA/C) at 12 months of age. Using Pearson's correlation method to assess the effect of pre-booster MenC-IgG concentration on the relative increase in MenC-IgG concentration post-booster, a significant negative correlation was observed for all the groups, indicating that high pre-booster antibody was associated with a smaller rise in antibody post-booster. We tested two additional statistical methods that account for mathematical coupling. Using Blomqvist method of adjustment to assess the plausible extent of bias, correlation coefficients were still negative providing error variance was low. The other method, a multilevel modelling specification of Oldham's method appeared not to be appropriate. In contrast, using Pearson's correlation method a consistent negative correlation between carrier protein-specific baseline antibody concentration and the increase in MenC-specific antibody concentration was only observed following booster immunisation with the protein-polysaccharide conjugate vaccine but not following the MenA/C plain polysaccharide vaccine. These findings suggest that analysis of the inhibitory effect of baseline antibody on the response to booster immunisation is challenging and should account for the possibility of mathematical coupling and measurement error. That an inhibitory effect of baseline antibody cannot be assumed a priori is supported by observations in animal models, which show that baseline antibody can both suppress or enhance the antibody response to a specific antigen.